Good Corporate Governance and Business Scale: Their Impact on Company Financial Performance - Rusmaya, Devita Rizki; Rahmah, Mulia; Loen, Mishelei (SAN Scientific, 2025)
This study examines the effect of institutional ownership, managerial ownership, and company size on the financial performance of healthcare companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using a quantitative approach with secondary data from the annual reports of 11 selected healthcare firms, the study analyzes how ownership structure and firm scale influence performance. The results show that institutional ownership, managerial ownership, and company size each have a negative impact on financial performance. However, when tested simultaneously, the three variables significantly affect financial performance. These findings suggest that ownership structure and firm size do not necessarily enhance performance, as they may also reflect governance complexities and variations in resource management efficiency. The study implies that healthcare firms should strengthen internal governance and develop more efficient ownership policies to ensure sustainable value creation. The originality of this research lies in its focus on Indonesia’s healthcare sector during the post-pandemic recovery period, an area seldom explored in prior studies particularly those combining ownership structure and firm size in a sector shaped by regulatory dynamics and service-based operational characteristics.